BASIC DIFFERENCES IN VILLAGE AUTHORITY ACCORDING TO LAW NUMBER 32 OF 2004, LAW NUMBER 23 OF 2014 WITH LAW NUMBER 6 OF 2014 - Hendri Wijaya, Junior; Mardhika, Juang Gagah (CV The Journal Publishing, 2024)
This study aims to analyze the differences in village authority in three laws, namely Law Number 32 of 2004, Law Number 23 of 2014, and Law Number 6 of 2014. The research method used is a descriptive-analytical approach by describing and analyzing the content of the law. The results of the analysis show that there are several changes and additions to village authority in Law Number 23 of 2014 and Law Number 6 of 2014, such as authority in village financial management, natural resources and environmental management, and authority in village development. However, some village authorities are removed or regulated more limited in Law Number 23 of 2014 and Law Number 6 of 2014. In conclusion, the changes and additions to village authority in Law Number 23 of 2014 and Law Number 6 of 2014 indicate an effort to give more authority and autonomy to villages in managing resources and development in their areas.